Bat hider image steganography using multiple OLSB substitution and multiple improved bat algorithm - Telimban, Antonio Jr. S.; Ultra, John D. (2015)
Increasing the robustness of the stego-object is the main problem in steganography especially when the size of the secret information increases. Also, middle-men attackers should not be able to extract the secret information like pseudo secret image even if they kbow the embedding process. There are already many approaches that have been used for increasing the robustness, imperceptibility and security in image steganography. In this thesis, the Optimal Least Significant Bit (OLSB) Substitution technique was used to embed the secret message in digital images. Multiple substitution matrix or vector of OLSB were used in the embedding process to increase the robustness and security of the stego-image. Moreover, a modified Hybrid Bat Algorithm was used to find the optimal set of substitution vectors/matrices. The proposed approach was able to prevent the extraction of a secret image called pseudo secret image using arbitrary substitution vectors that is present in previous applications of OLSB that did not use encrypted secret image data. The experiments showed that the method used has also increased the robustness, imperceptibility and security of stego-images.
Undergraduate thesis (B.S. Computer Science) -- University of the Philippines, Tacloban.
Keywords: Steganography; Bat Algorithm